Comparison of Electrochemical Behaviors between FSW and MIG Joints for 6082 Aluminum Alloy. Issue 2 (February 2017) - Yong, Peng; Changbin, Shen; Yadong, Zhao; Ying, Chen
Abstract: Electrochemical corrosion behaviors of friction stir welding (FSW) and MIG (mixed inert gas) welding joints of 6082 Al alloy and parent material 6082 Al alloy were investigated in a solution of 0.2 mol/L NaHSO3 and 0.6 mol/L NaCl, by potentiodynamic polarization curve, electrochemical impedance spectroscopy (EIS) and scanning electron microscopy (SEM) observation. Results show that the corrosion rate of the FSW joint is less than those of MIG joint and the parent material; the corrosion potential of the FSW joint is more positive than those of MIG joint and the parent material; the corrosion current density of the FSW joint is less than those of MIG joint and the parent material; the polarization resistance of the FSW joint is greater than those of MIG joint and the parent material. EIS Nyquist loops indicate that an inductive arc exist on the complex plane. SEM observation shows that a few shallow pits occurs on the surface of the FSW joint; however, a large number of deeper pits appear on the surface of the parent materials and MIG joint.